Changesin Carbon to Nitrogen Ratio (C/N) in Peatlands of Pontianakas Influenced by Land Management Duration - Alhaddad, Abdulmujib (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Peatland farmers in Pontianak have traditionally applied combustion ash and organic matter to increase soil pH and nutrient availability, thereby enhancing crop productivity. Poultry manure is essential for providing essential macro- and micronutrients. Although changes in peat soil properties due to agricultural use are known, the specific attributes affected and the magnitude of these changes remain poorly documented. This study aimed to: (1) determine changes in the carbon-to-nitrogen (C/N) ratio in peat soils cultivated under different land management practices, and (2) assess temporal changes in the C/N ratio associated with different cultivation durations. The study employed a direct survey method. Results showed that differences in peat soil characteristics between managed and unmanaged land were primarily evident in the 0–20 cm and 20–40 cm layers. Changes in the C/N ratio were caused by intensive management practices involving large amounts of combustion ash, fish waste, shrimp shells, lime, urea, and KCl. In general, management duration did not significantly affect the C/N ratio or other chemical properties, except for KED and base saturation. At depths of 40–80 cm, the management effect is negligible, indicating that topsoil interventions have only limited impact on deeper layers. The relative stability of nutrient status in Pontianak's peatlands, despite prolonged intensive inputs, demonstrates the resilience of peat soil fertility. Changes in land suitability characteristics are primarily driven by management practices rather than cultivation duration.